Implementation of the On-the-Job Training Learning Program for Students Majoring in Hospitality Accommodation - Anita Salsabila; Tran Huy Duc; Suwakhon Somphaiphithak (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to determine the implementation of the on-the-job training learning program for students majoring in hotel accommodation at Vocational High School 4 Jambi City. Methodology: This research uses a qualitative approach with a naturalistic approach. The population and sample in this study were students from Vocational High School 4 Jambi City. The data collection techniques in this research used documentation and interviews. Main Findings: From the results of research regarding the implementation of the On The Job Training learning program for students majoring in Hospitality Accommodation at Vocational High School 4 Jambi City, it can be concluded that this program has a significant positive impact on students' preparation to enter the world of work. The implementation succeeded in increasing students' practical understanding of work processes in the hotel industry, as well as helping students develop skills and knowledge that are relevant to job market demands. Novelty/Originality of this study: The novelty of this research lies in its specific focus on the implementation of on-the-job learning programs in the Hospitality Accommodation department, which is an important field in the hotel industry. This research will reveal how on the job programs are implemented in vocational education, identify challenges that may be faced, and evaluate effectiveness in preparing students to enter the world of work. It is hoped that this research will provide valuable insights for schools, industry and education policy to improve the relevance and quality of education in the future.